The Phenomenology of Remembering Is an Epistemic Feeling - Perrin, Denis; Michaelian, Kourken; Sant’Anna, André (Frontiers in Psychology, 2020)
This paper aims to provide a psychologically-informed philosophical account of the phenomenology of episodic remembering. The literature on epistemic or metacognitive feelings has grown considerably in recent years, and there are persuasive reasons, both conceptual and empirical, in favour of the view that the phenomenology of remembering—autonoetic consciousness, as Tulving influentially referred to it, or the feeling of pastness, as we will refer to it here—is an epistemic feeling, but few philosophical treatments of this phenomenology as an epistemic feeling have so far been proposed. Building on insights from the psychological literature, we argue that a form of feeling-based metacognition is involved in episodic remembering and develop an integrated metacognitive feeling-based view that addresses several key aspects of the feeling of pastness, namely, its status as a feeling, its content, and its relationship to the first-order memories the phenomenology of which it provides.